O complexo migmatítico de bemposta (nordeste transmontano de Portugal): implicações para a evolução do orógeno varisco - Martins, Fábio André Craveiro (2022)
In the Bemposta region, located in the northeastern Portugal, outcrops a Variscan Migmatitic Complex, known as Bemposta Migmatic Complex (BMC). The BMC is part of the Iberian Massif which represents the westernmost segment of the European Variscan Belt, formed during the collision between Gondwana and Laurussia and that culminated with formation of the super-continent Pangea, in the final of the Paleozoic. The Bemposta Migmatitic Complex (BMC) is an high-grade metamorphic belt composed by Douro group-derived stromatic migmatites and variably migmatized orthogneisses. These rocks showing evidences that were affected by partial melting during the second Variscan deformation event (D2). The anatexis culminated with intrusion of syn-tardi-D2 granites sills in the BMC. Field and petrographic evidences suggest that the anatexis of the metasediments was controlled by muscovite dehydration melting reactions. On the other hand, the stromatic leucosomes show evidences that were probably produced at a slightly deeper structural level (through biotite dehydration melting reaction) and subsequently injected in these terrains. The whole rock geochemical data shows that the leucosomes and granites derived mainly from partial melting of metasediments with similar composition to Douro Group. The geochemical data also reveals that leucosomes no longer corresponding to the original melt compositions. During melt migration and ascent, they were undergone fractional crystallization and accumulation of K-feldspar. Syn-tardi-D2 Leucogranites that intruded CMB, should have been produced by high degrees of partial melting. They have fractionated compositions and variable degrees of contamination with residual accessory mineral phases. Isotopic data (Sr-Nd) supports the idea that the Douro group metasediments are the main source material involved in the anatexis event and generation of granitic magmas in this sector. However, the εNd values and TDM ages suggest that melts derived from partial melting of orthogneisses may have contributed to the leucossome and granite petrogenesis. The SHRIMP U-Pb crystallization age obtained for this granite (324 ± 3 Ma) provides a good estimate for the age of the D2-anatectic event in the CMB metamorphic terrane.